A NEW ITERATIVE SOLVER FOR THE TIME-HARMONIC WAVE EQUATION - Riyanti C.D.; Erlangga Y.A.; Vuik C.; Oosterlee C.; Plessix R.-E.; Mulder W.A. (My University, 2006)
The time-harmonic wave equation, also known as the Helmholtz equation, is obtained if the constant-density acoustic wave equation is transformed from the time domain to the frequency domain. Its discretization results in a large, sparse, linear system of equations. In two dimensions, this system can be solved efficiently by a direct method. In three dimensions, direct methods cannot be used for problems of practical sizes because the computational time and the amount of memory required become too large. Iterative methods are an alternative. These methods are often based on a conjugate gradient iterative scheme with a preconditioner that accelerates its convergence. The iterative solution of the time-harmonic wave equation has long been a notoriously difficult problem in numerical analysis. Recently, a new preconditioner based on a strongly damped wave equation has heralded a breakthrough. The solution of the linear system associated with the preconditioner is approximated by another iterative method, the multigrid method. The multigrid method fails for the original wave equation but performs well on the damped version. The performance of the new iterative solver is investigated on a number of 2D test problems. The results suggest that the number of required iterations increases linearly with frequency, even for a strongly heterogeneous model where earlier iterative schemes fail to converge. Complexity analysis shows that the new iterative solver is still slower than a time-domain solver to generate a full time series. We compare the time-domain numeric results obtained using the new iterative solver with those using the direct solver and conclude that they agree very well quantitatively. The new iterative solver can be applied straightforwardly to 3D problems. © 2006 Society of Exploration Geophysicists.
Keywords: CONJUGATE GRADIENT METHODS; DIFFERENTIAL EQUATIONS; GEOPHYSICAL TECHNIQUES; HELMHOLTZ EQUATIONS; ITERATIVE METHODS; SEISMIC WAVES